Training Specialists on the Basis of the Credit-Module Training System - Ulkanov Sardor Sodikjon ugli (Zien Journals, 2022)
This is a credit module system essence, education to the system come in to arrive history and our republic higher education to the system current of reaching necessity about word goes. Also credit module in the system study plans, science programs and independent of education features given
Keywords: credit-module; credit-module system functions; methodology